Proceedings of the 21st ACM International Conference on Multimedia 2013
DOI: 10.1145/2502081.2502201
|View full text |Cite
|
Sign up to set email alerts
|

Correlated-spaces regression for learning continuous emotion dimensions

Abstract: Adopting continuous dimensional annotations for affective analysis has been gaining rising attention by researchers over the past years. Due to the idiosyncratic nature of this problem, many subproblems have been identified, spanning from the fusion of multiple continuous annotations to exploiting output-correlations amongst emotion dimensions. In this paper, we firstly empirically answer several important questions which have found partial or no answer at all so far in related literature. In more detail, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…Since surprise and happiness are generally expressed more exaggeratedly than anger and sadness, such as an open mouth, it seems that the correlation of arousal or valence dimension to an emotion is also correlated with the level of expression exaggeration of this emotion. This also agrees with the result in [6] which indicated that anger has lower correlation than happiness when predicted in continuous values using 2-D facial point features.…”
Section: Nvie Databasesupporting
confidence: 91%
See 3 more Smart Citations
“…Since surprise and happiness are generally expressed more exaggeratedly than anger and sadness, such as an open mouth, it seems that the correlation of arousal or valence dimension to an emotion is also correlated with the level of expression exaggeration of this emotion. This also agrees with the result in [6] which indicated that anger has lower correlation than happiness when predicted in continuous values using 2-D facial point features.…”
Section: Nvie Databasesupporting
confidence: 91%
“…A dimensional space can provide insight into the emotional intensity, as well as the similarity and contrast between different categorized emotions. Although emotion dimensions can be inherently more expressive in comparison to categorized emotions, no explicit mapping between the two descriptions has been established [6]. The correlation between dimensions and categorized emotions is more of an abstract and relatively ambiguous correspondence.…”
Section: Facial Expression Representationmentioning
confidence: 99%
See 2 more Smart Citations
“…using Support Vector Regression (SVR) etc. on image features [28], resulted in very poor performance. Hence, we implemented a deep neural network approach as the baseline.…”
Section: Experiments With a Baselinementioning
confidence: 99%